Pemanfaatan Generative Artificial Intelligence (GenAI) untuk Meningkatkan Minat Belajar Mahasiswa : Indonesia - Koroh, Tince Dormalin (Balai Diklat Keagamaan Denpasar, 2025)
Generative Artificial Intelligence (GenAI) is a technology that has the potential to increase efficiency in organizing interactive and non-boring learning so as to attract students to be more actively involved and contribute to the learning process. This study aims to descriptive quantitative with data analysis using percentages. The research subjects were IAKN Kupang students and Nusa Cendana University students class of 2025 totaling 104 respondents. Data collection with a questionnaire in the form of a statement with a Likert scale distributed using Google form. The results of the ChatGPT research are most widely used by students, in the aspect of feeling happy, students feel happy to use GenAI. In the aspect of interest, students are interested in using GenAI. In the awareness aspect, student feel that they are not very accomplished in using GenAI but they are eager to involve GenAI in class discussions and in the learning process, and the concentration aspect, students do use GenAI to find course material but they cannot remember the material longer. In assignments buat does not really make students exel because students are more likely to remember the material longer. In conclusion, GenAI is very liked and helps students in completing assigments buat does not really make students exel because students leave more assignments to be completed. Therefore, lectures need to design student learning tasks or activities that can improve learning achievements by using GenAI.